Childhood catatonia, autism and psychosis past and present: is there an 'iron triangle'?. (27th January 2013) - Shorter, E.; Wachtel, L. E.
<x xml:space="preserve">Abstract</x> Objective To explore the possibility that autism, catatonia and psychoses in children are different manifestations of a single underlying form of brain pathology – a kind of 'Iron Triangle' of symptomatology – rather than three separate illnesses. Method Systematic evaluation of historical case literature on autism to determine if catatonic and psychotic symptoms accompanied the diagnosis, as is found in some challenging present‐day cases. Results It is clear from the historical literature that by the 1920s all three diagnoses in the Iron Triangle – catatonia, autism and childhood schizophrenia – were being routinely applied to children and adolescents. Furthermore, it is apparent that children diagnosed with one of these conditions often qualified for the other two as well. Although conventional thinking today regards these diagnoses as separate entities, the presence of catatonia in a variety of conditions is being increasingly recognized, and there is also growing evidence of connections between childhood‐onset psychoses and autism. Conclusion Recognition of a mixed form of catatonia, autism and psychosis has important implications for both diagnosis and treatment. None of the separate diagnoses provides an accurate picture in these complex cases, and when given single diagnoses such as 'schizophrenia', the standard treatment options may prove markedly ineffective.